Determining the Optimal Density of Neka Using Fractal Method and the Study of Its Geological Situation - Hamzei, Azadeh; Teymoorian, Asghar (International Journal of Geography and Geology, 2015)
In discovery geophysics, the primary aim is to determine the density of the studied targets which have definite density difference from host rocks. In this study, we express a method to determine the density of Bouguer plane, called fractal method. This method is based on minimization of surface roughness of Bouguer anomaly. From fractal dimension, the surface is used as a roughness criterion of Bouguer anomaly. Using this method, we can determine the optimum density of Neka region to use for modifications and monitoring the results in isostatic situation of region.